FEAR OF GOD AND ACADEMIC ACHIEVEMENT: A CORRELATIONAL STUDY AMONG TENTH GRADE STUDENTS AT GKPI PADANG BULAN PRIVATE SENIOR HIGH SCHOOL IN MEDAN, 2023 - Saragih, Novita Romauli; Sitepu, Elisabeth; Karo-Karo, Selamat; Sitohang, Riama; Wiharjokusumo, Padriadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Penelitian ini mengkaji korelasi antara sikap